Characterization of a CO-dependent O-demethylating enzyme system from the acetogen Clostridium thermoaceticum. - Wu, Z R (1988)
An inducible O-demethylating enzyme system was characterized from Clostridium thermoaceticum cultivated at the expense of syringate. Glucose and methanol, but not CO, partially repressed its expression. Induced whole cells catalyzed the carbon monoxide (CO)-dependent O demethylation of methoxylated aromatic compounds with the concomitant formation of acetate. Pyruvate and, to a lesser extent, H2-CO2 could replace CO in these reactions. KCN inhibited pyruvate-dependent activity but not the CO-dependent activity. The ATPase inhibitor N,N'-dicyclohexylcarbodiimide, the protonophore carbonyl cyanide m-chlorophenylhydrazone, and methyl viologen did not appreciably inhibit O demethylation by induced cells, whereas Triton X-100 was inhibitory. The enzyme system appeared to convert syringate sequentially to 5-hydroxyvanillate and gallate. The proposed overall reaction stoichiometry was as follows: syringate + 2CO + 2H2O----gallate + 2 acetates. Growth-supportive methoxylated aromatic compounds were O demethylated by syringate-cultivated cells and inhibitory to syringate O demethylation.